Gene molecular analysis and Adiponectin expression in professional Water Polo players. (May 2016) - Nigro, Ersilia; Sangiorgio, Dino; Scudiero, Olga; Monaco, Maria Ludovica; Polito, Rita; Villone, Giovanni; Daniele, Aurora
Highlights: High-intensity sports as Water polo exert long-term beneficial effects on metabolism. Water Polo does not modify adiponectin and/or HMW expression in athletes. Adiponectin may participate in exercise-induced anti-inflammatory functions. Abstract: Metabolic Syndrome prevalence has reaching epidemic proportions worldwide. Adiponectin (Acrp30), and in particular its High Molecular Weight (HMW) oligomers, contributes to enhance insulin sensitivity and to reduce inflammation levels. Physical exercise improves body's biochemical balance and metabolism resulting effective in prevention of metabolic diseases. Whether improvement of metabolic features mediated by physical exercise is associated with changes in Acrp30 serum composition is not yet clarified. In the present study, we investigated total Acrp30 expression, its oligomeric status and genetic variants in adiponectin gene (ACDC) in twenty-two professional Water Polo (WP) Players and 40 age- and sex-matched controls. Anthropometric, metabolic parameters and total Acrp30 were assessed; Acrp30 oligomeric profile was characterized by Western blot as well as by FPLC analysis. ACDC gene was analyzed by direct-sequencing analysis. Significant elevated body mass index, aspartate aminotransferase and lactate dehydrogenase levels and, conversely, significantly lower concentrations of total and cholesterol low density lipoprotein were present in WP players. No significant difference was found in total Acrp30 and/or HMW oligomers. Interestingly, in WP players, a direct relationship between total Acrp30 and monocytes as well as an inverse relationship between total Acrp30 and AST levels were found. ACDC screening revealed previously described SNPs. In conclusion, our study confirms the long-term beneficial effects of high physical training on metabolism and suggests that they are not associated with Acrp30 and/or HMW oligomers changes. Moreover, the correlation of Acrp30 with monocytes in WP athletes could represent a mechanism by which Acrp30 participates in exercise-induced anti-inflammatory functions and/or cardiovascular health.